2011
DOI: 10.1007/s11096-011-9518-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 36-month pharmaceutical care program on pharmacotherapy adherence in elderly diabetic and hypertensive patients

Abstract: These results indicated the effectiveness of pharmaceutical care in improving pharmacotherapy adherence, with positive effects in the clinical outcomes of the patients studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 24 publications
7
108
2
2
Order By: Relevance
“…A recent study conducted in Goiás between 2000 and 2008 showed that 17.2% of hospitalizations occurred as a result of cardiovascular conditions that could have been resolved at primary level (Batista et al, 2012). Therefore, Pharmaceutical Care may represent an important tool within the FHS, benefitting patients with hypertension by controlling their blood pressure (Castro et al, 2006;Lyra Júnior et al, 2008;Morgado et al, 2011;Obreli-Neto et al, 2011, Aguiar et al, 2012b, improving adherence to antihypertensive drugs (Souza et al, 2007;Aguiar et al, 2012b) and optimizing metabolic control of carbohydrates and lipids (Kicklighter et al, 2006;Correr et al, 2011;Obreli-Neto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted in Goiás between 2000 and 2008 showed that 17.2% of hospitalizations occurred as a result of cardiovascular conditions that could have been resolved at primary level (Batista et al, 2012). Therefore, Pharmaceutical Care may represent an important tool within the FHS, benefitting patients with hypertension by controlling their blood pressure (Castro et al, 2006;Lyra Júnior et al, 2008;Morgado et al, 2011;Obreli-Neto et al, 2011, Aguiar et al, 2012b, improving adherence to antihypertensive drugs (Souza et al, 2007;Aguiar et al, 2012b) and optimizing metabolic control of carbohydrates and lipids (Kicklighter et al, 2006;Correr et al, 2011;Obreli-Neto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this is the picture of the Brazilian public health system, thus no non-pharmacological intervention is performed and the burden is attributed only to the medicines to control diabetes. In this baseline, pharmaceutical care comes as a powerful tool to control glycemic levels and improves the adherence to treatment in patients with chronic diseases including diabetes [26][27][28][29][30]. Recently our group published two review articles that showed that a change in the current medical model is needed and to investigate other factors such as toxins, malnutrition, stress, infections and electromagnetic pollution in patients with chronic diseases [26,31].…”
Section: Discussionmentioning
confidence: 99%
“…Estimation on patient adherence to the use of dabigatran was done through the method of recording drug removal described by Obreli-Neto et al (2011), 13 and patients considered as having adhered were those with an agreement level of 80 to 115%.…”
Section: Methodsmentioning
confidence: 99%